2011
DOI: 10.1007/s11661-011-0889-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Microstructure and Texture During Hot Compression of a Ni-Fe-Cr Superalloy

Abstract: Superalloys are being employed in more extreme conditions requiring higher strength, which requires producers to forge products to finer grain sizes with less grain size variability. To assess grain size, crystallographic texture, and substructure as a function of forging conditions, frictionless uniaxial compression testing characteristic of hot working was performed on INCOLOY 945 (Special Metals Corporation, Huntington, WV), which is a newly developed hybrid of alloys 718 and 925, over a range of temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…It appears that the grains in the Alloy A in the as-annealed sample have stronger orientations (Figure 5a, a double fiber texture with 110 and 111 ) compared to Alloy B (Figure 5b, a fiber texture with 100 ) [41]. Alloy A also exhibits a fiber compression texture 110 , which is consistent with other materials that have face-centered cubic crystal structures [43]. This is also consistent with stress-strain curves for the deformation tests (Figure 3).…”
Section: Microstructure Analysis 421 Microstructure Before Deformationsupporting
confidence: 56%
“…It appears that the grains in the Alloy A in the as-annealed sample have stronger orientations (Figure 5a, a double fiber texture with 110 and 111 ) compared to Alloy B (Figure 5b, a fiber texture with 100 ) [41]. Alloy A also exhibits a fiber compression texture 110 , which is consistent with other materials that have face-centered cubic crystal structures [43]. This is also consistent with stress-strain curves for the deformation tests (Figure 3).…”
Section: Microstructure Analysis 421 Microstructure Before Deformationsupporting
confidence: 56%
“…[ 40 ] It is also widely reported that the formation of annealing twins can lower the boundary energy of growing grain and increase the mobility of the grain boundary. [ 41 ] Thus, the process of DRX is promoted by the Σ3 boundary. Specifically, the anomalous grain growth may result in nucleation in subgrain boundaries with misorientation lower than 2° at 1200 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The DRX is classified into two categories according to phenomenological classification, i.e., DDRX and CDRX. [ 41 ] The process of CDRX is considered as a dominant nucleation mechanism for the nickel‐based superalloy at low temperature and high strain rate, as discussed previously. It involves the procedures of LAGB array and rearrangement of dislocations during hot deformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was interesting to note that a load drop and secondary yield point were visible on the flow curves of the initial deformation stage at the strain rate of 10 −1 s −1 (Figure 2c,d). This phenomenon is also observed in Ti60 alloy [26] and superalloys [27,28], which could be caused by microstrain dynamic strain aging. Figure 2d,h shows that the flow curves with dynamic recrystallization characteristics were observed at the strain rate of 10 −3 s −1 , indicating that the alloys with two different grain sizes had undergone dynamic recrystallization under these deformation conditions.…”
Section: Methodsmentioning
confidence: 64%